Faktor-Faktor Yang Mempengaruhi Perusahaan Melakukan Auditor Switching (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Susanto, Oky Palasari; , Fauzan, SE, M.Si, Akt (2015)
Auditor switching is a changes of auditor performed by the client company. The purposes of this research are to analyze the influence of audit opinion, management changes, KAP size, client size, and financial distress on the auditor switching manufacturing companies listed on the Indonesia Stock Exchange. The population used in this study focused on manufacturing companies listed in Indonesia Stock Exchange 2010-2014. Sampling was purposive sampling method that produced 75 companies sample. Data analysis technique used is logistic regression analysis. The results of the study showed that audit opinion affect to the auditor switching. Management changes, KAP size, client size, and financial distress has no affect to the auditor switching. Keywords: auditor switching, audit opinion, management changes, KAP size, client size, and financial distress.